2005
DOI: 10.1542/peds.2004-1405
|View full text |Cite
|
Sign up to set email alerts
|

Primary Operative Versus Nonoperative Therapy for Pediatric Empyema: A Meta-analysis

Abstract: These aggregate results suggest that primary operative therapy is associated with a lower in-hospital mortality rate, reintervention rate, length of stay, time with tube thoracostomy, and time of antibiotic therapy, compared with nonoperative treatment. The meta-analysis demonstrates a significantly reduced relative risk of failure among patients treated operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
6
20

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 61 publications
10
127
6
20
Order By: Relevance
“…In a meta-analysis of 67 studies done by Avansino et al it was observed that Patients who underwent primary operative therapy had a lower aggregate in-hospital mortality rate (0% vs 3.3%), re-intervention rate (2.5% vs 23.5%), length of stay (10.8 vs 20.0 days), duration of tube thoracostomy (4.4 vs 10.6 days), and duration of antibiotic therapy (12.8 vs 21.3 days), compared with patients who underwent non-operative therapy [4]. We found similar findings of aggregate in-hospital mortality rate (0%), re-intervention rate (0%), length of stay (8.26 days), duration of tube thoracostomy (4.53 days) in our study.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a meta-analysis of 67 studies done by Avansino et al it was observed that Patients who underwent primary operative therapy had a lower aggregate in-hospital mortality rate (0% vs 3.3%), re-intervention rate (2.5% vs 23.5%), length of stay (10.8 vs 20.0 days), duration of tube thoracostomy (4.4 vs 10.6 days), and duration of antibiotic therapy (12.8 vs 21.3 days), compared with patients who underwent non-operative therapy [4]. We found similar findings of aggregate in-hospital mortality rate (0%), re-intervention rate (0%), length of stay (8.26 days), duration of tube thoracostomy (4.53 days) in our study.…”
Section: Discussionmentioning
confidence: 91%
“…4 Incomplete drainage of the pleural space will result in persistent infection which would lead to functional impairment and substantial morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta analysis comparing operative and non-operative procedures has concluded that conservative management leads to recovery in more than 76% of the patients [22]. However, it needs to be emphasised that a less invasive primary operative procedure like drainage with lavage-irrigation has the potential to interrupt the progression of empyema, decrease discomfort associated with prolonged thoracostomy tube usage and reduce the total duration of hospital stay and chest tubes in situ.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated decreased re-intervention rates and time with chest tube in place, shorter duration of antibiotic therapy, shorter length of stay, and decreased inhospital mortality rates with initial operative management [75]. One multicenter study of US children's hospitals compared outcomes for patients treated with a variety of drainage procedures including thoracotomy, chest tube placement with and without fibrinolytics, and videoassisted thoracoscopic surgery (VATS).…”
Section: Treatment Of Complicated Diseasementioning
confidence: 97%